Strategic Decomposition: How to Increase Total Labor Productivity - Tsuchida, Shu (International Journal of Contemporary Economics and Administrative Sciences, 2016)
Labor productivity is a key indicator in economic analysis. Numerous aggregative formulae exist for calculating labor productivity growth at the firm-level, with the result that the contribution of each firm to total labor productivity growth varies according to the formulae used in its calculation. In this study, we systematically derive many aggregative formulae. Using one of these formulae, we examine the link between labor productivity growth at the firm-level and that at the industry-level, and identify the situations in which the former is not correlated with the latter. A central concept in this study is the clarification of a strategic decomposition. Our strategic decomposition uses a very simple formula and can be used to solve the problem of maximizing the increase of total labor productivity for a few years. We use numerical examples to illustrate new methods for solving this problem.